Manganese doping on biphasic calcium phosphate ceramics for machanical improvement - Sopyan, Iis (Malaysian Medical Associations, 2010)
SUMMARY Manganese doped biphasic calcium phosphate powders have been synthesized via sol-gel method. The powders are of nanosize and high crystallinity. Dense pure BCP and Mn-doped BCP ceramics were fabricated via uniaxial pressing using the sol-gel derived powders. The compacted discs were sintered in air atmosphere with temperatures ranging from 1000 ºC to 1400 ºC. The presence of manganese improves the densification in the BCP mixture as the relative density increased with Mn doping and also sintering temperature. Considerable grain growth has been observed at 1300 ºC for Mn-doped BCP samples compared to the pure BCP. Furthermore, 15 mol% Mn showed the maximum hardness value of 6.66 GPa at 1400 ºC compared to pure BCP of only 2.89 GPa. Similarly, the Mn-doped BCP has superior fracture toughness where it attained maximum values of 1.05 MPam1/2 at 1400 ºC compared to 0.72 MPam1/2 at 1300 ºC of pure BCP.